PENGARUH PRICE DAN KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN APLIKASI MAXIM (S TUDI MAHASISWA PEMASARAN SEMESTER 7 UNIVERSITAS PAMULANG) - Mad Nawin Alhadi; Asep Sulaeman (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
This study aims to determine the effect of Price and Service Quality on Customer Satisfaction of the Maxim application (a study of 7th-semester Marketing students at Pamulang University), both partially and simultaneously. The research method used is a quantitative associative approach. The population in this study consists of 7th-semester marketing students at Pamulang University, with a total of 98 respondents selected through purposive sampling. Primary data were collected through questionnaires and analyzed using SPSS version 27. The tests conducted include validity and reliability tests, classical assumption tests, multiple linear regression analysis, t-test, F-test, and coefficient of determination. The results show that price has a positive and significant partial effect on customer satisfaction, with a calculated t-value of 2.655 > 1.661 and a significance value of 0.003 < 0.05. Service quality also has a positive and significant partial effect on customer satisfaction, with a calculated t-value of 9.130 > 1.661 and a significance value of 0.000 < 0.05. Furthermore, price and service quality simultaneously have a positive and significant effect on customer satisfaction, with an F-value of 47.891 > 3.092 and a significance value of 0.000 < 0.05. The conclusion of this study is that there is a positive and significant effect, both partially and simultaneously, between price and service quality on customer satisfaction of the Maxim application (a study of 7th-semester Marketing students at Pamulang University).